Late-onset neutropenia after treatment with rituximab for rheumatoid arthritis and other autoimmune diseases: data from the AutoImmunity and Rituximab registry. Issue 1 (30th June 2015) - Salmon, J H; Cacoub, P; Combe, B; Sibilia, J; Pallot-Prades, B; Fain, O; Cantagrel, A; Dougados, M; Andres, E; Meyer, O; Carli, P; Pertuiset, E; et al.
Abstract : Objectives: To evaluate the prevalence of late-onset neutropenia and its complications in patients treated with rituximab (RTX) for rheumatoid arthritis (RA) and other autoimmune diseases (AIDs) in a prospective registry. Methods: The AutoImmunity and Rituximab registry is an independent 7-year prospective registry promoted by the French Society of Rheumatology. For each episode of neutropenia, data were validated by the clinician in charge of the patient. Results: Among 2624 patients treated with RTX for refractory AIDs, and at least 1 follow-up visit (a total follow-up of 4179 patient-years in RA and 987 patient-years in AIDs), late-onset neutropenia was observed in 40 patients (25 RA (1.3% of patients with RA, 0.6/100 patient-years), and AIDs in 15 (2.3% of patients with AIDs, 1.5/100 patient-years)). 6 patients (15%) had neutrophils <500/mm 3, 8 (20%) had neutrophils between 500 and 1000/mm 3, and 26 (65%) had neutrophils between 1000 and 1500/mm 3 . Neutropenia occurred after a median period of 4.5 (3–6.5) months after the last RTX infusion in patients with RA, and 5 (3–6.5) months in patients with AIDs. 5 patients (12.5%), 4 of them with neutrophils lower than 500/mm 3, developed a non-opportunistic serious infection and required antibiotics and granulocyte colony-stimulating factor injections, with a favourable outcome. After resolution of their RTX-related neutropenia, 19 patients (47.5%) were re-treated, and neutropenia reoccurred in 3 of them. Conclusions: Late-onset neutropenia might occur after RTX and may result in serious infections. Thus, monitoring of white cell count should be performed after RTX. However, in this large registry of patients with AIDs, the frequency of RTX-induced neutropenia was much lower than that previously reported in patients treated for blood malignancies or AIDs.